2018
DOI: 10.1371/journal.pntd.0006260
|View full text |Cite
|
Sign up to set email alerts
|

Taenia solium, Taenia saginata, Taenia asiatica, their hybrids and other helminthic infections occurring in a neglected tropical diseases' highly endemic area in Lao PDR

Abstract: Most part of Southeast Asia is considered endemic for human-infecting Taenia tapeworms; Taenia solium, T. saginata, and T. asiatica. However, until now there was no report of the occurrence of human cases of T. asiatica in Lao PDR. This study, conducted in Savannakhet Province, Lao PDR, microscopically examined a total of 470 fecal samples by Kato Katz method and found 86% of people harboring at least one helminth. Hookworms were detected in 56% of the samples besides Opisthorchis like eggs (42%), Trichuris tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 35 publications
0
30
0
3
Order By: Relevance
“…Following these early discoveries, methods for assaying numerous individuals for their nuclear genotype became more widely available to researchers and, subsequently, the number of cases increased markedly in animals such as mammals, birds, reptiles, amphibians, fish, and insects [ 37 ]. More recent studies revealed that mito-nuclear discordance occurs in helminth parasites [ 40 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following these early discoveries, methods for assaying numerous individuals for their nuclear genotype became more widely available to researchers and, subsequently, the number of cases increased markedly in animals such as mammals, birds, reptiles, amphibians, fish, and insects [ 37 ]. More recent studies revealed that mito-nuclear discordance occurs in helminth parasites [ 40 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al successfully used cox1 to distinguish between T. saginata and T. asiatica [11]. Recently, studies conducted in China and Lao People’s Democratic Republic reported that hybridization between the three Taenia species cab iccyr, based on sequencing nuclear and mitochondrial genes [19, 20]. In our case, as we did not observe uterine structures or ova in the proglottids in our patient’s stool sample, these proglottids were likely immature.…”
Section: Discussionmentioning
confidence: 59%
“…The important helminthes are soil transmitted helminthes (STHs), foodborne helminthes and schistosomes occurring mostly in areas of low-income inhabitants with sub-standard sanitation. Interestingly, people are aware of parasitic disease; however, there is a sentiment that the infection is unavoidable and the treatment uncertain, thus leading to high rates of helminth infection and heavy worm burden (Sato et al, 2018a).…”
Section: The Persistence Of Helminths and Its Consequencesmentioning
confidence: 99%